Genetic and Epigenetic Differentiation Across Intertidal Gradients in the Foundation Plant Spartina alterniflora - Mounger, Jeannie M.; van Riemsdijk, Isolde; Boquete, M. Teresa; Wagemaker, Cornelis A. M.; Fatma, Samar; Robertson, Marta H.; Voors, Sandy A.; Oberstaller, Jenna; Gawehns, Fleur; Hanley, Torrance C.; Grosse, Ivo; Verhoeven, Koen J. F.; et al. (Frontiers in Ecology and Evolution, 2022)
Ecological genomics approaches have informed us about the structure of genetic diversity in natural populations that might underlie patterns in trait variation. However, we still know surprisingly little about the mechanisms that permit organisms to adapt to variable environmental conditions. The salt marsh foundation plant Spartina alterniflora exhibits a dramatic range in phenotype that is associated with a pronounced intertidal environmental gradient across a narrow spatial scale. Both genetic and nongenetic molecular mechanisms might underlie this phenotypic variation. To investigate both, we used epigenotyping-by-sequencing (epiGBS) to evaluate the make-up of natural populations across the intertidal environmental gradient. Based on recent findings, we expected that both DNA sequence and DNA methylation diversity would be explained by source population and habitat within populations. However, we predicted that epigenetic variation might be more strongly associated with habitat since similar epigenetic modifications could be rapidly elicited across different genetic backgrounds by similar environmental conditions. Overall, with PERMANOVA we found that population of origin explained a significant amount of the genetic (8.6 %) and epigenetic (3.2 %) variance. In addition, we found that a small but significant amount of genetic and epigenetic variance (< 1 %) was explained by habitat within populations. The interaction of population and habitat explained an additional 2.9 % of the genetic variance and 1.4 % of the epigenetic variance. By examining genetic and epigenetic variation within the same fragments (variation in close-cis), we found that population explained epigenetic variation in 9.2 % of 8,960 tested loci, even after accounting for differences in the DNA sequence of the fragment. Habitat alone explained very little (< 0.1 %) of the variation in these close-cis comparisons, but the interaction of population and habitat explained 2.1 % of the epigenetic variation in these loci. Using multiple matrix regression with randomization (MMRR) we found that phenotypic differences in natural populations were correlated with epigenetic and environmental differences even when accounting for genetic differences. Our results support the contention that sequence variation explains most of the variation in DNA methylation, but we have provided evidence that DNA methylation distinctly contributes to plant responses in natural populations.